Making Moral Judgments Psychological Perspectives on Morality, Ethics, and Decision-Making - Forsyth, Donelson (Taylor & Francis, 2020)
This fascinating new book examines diversity in moral judgements, drawing on recent work in social, personality, and evolutionary psychology, reviewing the factors that influence the moral judgments people make. Why do reasonable people so often disagree when drawing distinctions between what is morally right and wrong? Even when individuals agree in their moral pronouncements, they may employ different standards, different comparative processes, or entirely disparate criteria in their judgments. Examining the sources of this variety, the author expertly explores morality using ethics position theory, alongside other theoretical perspectives in moral psychology, and shows how it can relate to contemporary social issues from abortion to premarital sex to human rights. Also featuring a chapter on applied contexts, using the theory of ethics positions to gain insights into the moral choices and actions of individuals, groups, and organizations in educational, research, political, medical, and business settings, the book offers answers that apply across individuals, communities, and cultures. Investigating the relationship between people's personal moral philosophies and their ethical thoughts, emotions, and actions, this is fascinating reading for students and academics from psychology and philosophy and anyone interested in morality and ethics.